The Value of Flexibility in the Italian Water Service Sector: A Real Option Analysis - Michele Moretto; Chiara D'Alpaos (Fondazione Eni Enrico Mattei (FEEM), 2004)
We analyze the optimal investment strategy of a monopolist which has subscribed a concession contract to provide a public utility, i.e. water service. We present a strategic model in which a monopolist chooses both the timing of the investment and the capacity. We focus not only on the value of the immediate investment, but rather on the value of the investment opportunity. We then extend the model to two interdependent projects, where investing in the first project provides the opportunity to acquire the benefits of the new investment by making a new outlay. We show that flexibility to defer an investment may generate, ceteris paribus, additional profits which may induce positive effects in terms of policy and consumers surplus.
Keywords: D81; G31; L95; 330; Irreversible investment; Flexibility to defer; Capacity expansion choice; Wasserversorgung; Wasserwirtschaft; Investitionsentscheidung; Monopol; Kapazitätsplanung; Italien